Soil moisture and its relation to crops - Umberger, Harry (My University, 1905)
Introduction: While generally the soil of Kansas is said to be abundantly rich in all the essential elements of plant life and. the climate well adapted to the growth of, plants, yet in many localities in Central Kansas each ear we find light crops and thought they seem to have been carefully cultivated, yet the yield was small and the farmer generally attributed it to lack of sufficient moisture. Most of the leading Agriculturists of the state claim, however, that in all parts of the state, excepting possibly the extreme western portion, there is sufficient moisture to mature a large crop but that the fault is with the fanner who fails to properly conserve and economize that moisture which is at his disposal and. as a result, of his excessive waste of moisture the crop is short. Of course before the farmer can economize soil moisture he must have it to economize, that is, there must be sufficient rainfall each year to mature the desired crop, and then when this condition is fulfilled it remains for him to use all the means in his power to use the water to the greatest advantage and this is done by proper cultivation and crop management with a view of determining as near as possible the amount of moisture at the disposal of the crop for the three months of April, May and June, I took a series of ten soil samples on the Kansas State Agricultural College farm. The samples were taken at the depth of feet, 'out only the first four samples were used finally, as the root system does not extend below this very often and though capillarity
Citation: Umberger, Harry. Soil moisture and its relation to crops. Senior thesis, Kansas State Agricultural College, 1905.
Morse Department of Special Collections
Keywords: Description of Soil; Description of Tools; Calculation of Data; Theses